Treatment of latent M. tuberculosis infection and use of antiretroviral therapy to prevent tuberculosis - Sterling, Timothy R.; Lin, Philana Ling (The Journal of clinical investigation, 2020)
Even with treatment of HIV with antiretroviral therapy (ART), the risk of tuberculosis (TB) reactivation remains higher in HIV-infected than HIV-uninfected persons. In this issue of the JCI, Ganatra et al. explored TB reactivation in the context of ART using TB and simian immunodeficiency virus-coinfected (TB/SIV-coinfected) nonhuman primates. The authors found that treating rhesus macaques with ART restored CD4+ T cells in whole blood, spleen, and bronchoalveolar lavage (BAL) fluid, but not in the lung interstitium. TB risk was not decreased in the coinfected macaques treated with ART for 14-63 days, suggesting that ART does not decrease the short-term risk of reactivation. Reactivation occurred as CD4+ T cells were increasing, which is consistent with observations made in humans. This study provides a potential model for systematic evaluation of TB/SIV coinfection and different treatment regimens and strategies to prevent TB reactivation.